A Case of Recurrent Acute Encephalopathy with Febrile Convulsive Status Epilepticus with Carnitine Palmitoyltransferase II Variation - Sakai, Eiko; Yamanaka, Gaku; Kawashima, Hisashi; Morishima, Yasuyuki; Ishida, Yu; Oana, Shingo; Miyajima, Tasuku; Shinohara, Mayu; Saitoh, Makiko; Mizuguchi, Masashi (Neuropediatrics, 2013)
Acute encephalopathy with febrile convulsive status epilepticus (AEFCSE) is the most common type of acute encephalopathy in childhood in Japan, which develops with prolonged febrile convulsion, followed by mild unconsciousness. It is generally sporadic and nonrecurrent. In this report, a 1-year-old girl showed signs of AEFCSE triggered by respiratory syncytial virus infection. Two years later, she presented with AEFCSE triggered by influenza virus infection, resulting in severe neurologic sequelae. The patient had a thermolabile genotype of carnitine palmitoyltransferase II (CPT II) variations consisting of three single nucleotide polymorphisms in exons 4 [1055T > G/F352C and 1102G > A/V368I] and 5 [1939A > G/M647V]. The polymorphism has been identified as a genetic predisposition for acute encephalopathy. This report presents the first case of recurrent encephalopathy with CPT II variations that may partially associate with pathogenesis of recurrent AEFCSE.
Keywords: recurrent encephalopathy; carnitine palmitoyltransferase II; AEFCSE; influenza virus; RS virus; cytokine